DESIGN OF INDONESIAN NAVY PERSONAL EQUIPMENT MONITORING SYSTEM BASED ON ANDROID MODEL - Sunarta Sunarta; Alexander Victor Bukit; Arie Marbandi; Kusdianto Kusdianto (JOURNAL ASRO, 2020)
Kaporlap is individual equipment that is attached to the body of a soldier, including all accessories, ranging from headgear, body cover to leg cover. These individual equipment were distributed so that each soldier could carry out basic tasks or routine daily tasks and the additional tasks provided could run well. Design and Development of the Navy-based College of Technology Kaporlap Monitoring System (STTAL) Android-based is an information system designed to make it easier for Kaur warehouse to make a report to the Kadeprenalog to find out stock information available at Renalog warehouse when it will distribute Kaporlap to Personnel and Students. Data collection methods used in the preparation of this final project are field studies and literature. After being identified, the authors designed the Kaporlap inventory system with systems development models such as context diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD) through to Input and Output designs, then proceed with the making of its web program and after that it can uploaded to the android system. After the whole system process is complete, it can be seen that the inventory system can produce information for official needs accurately and quickly.Keywords : Kaporlap Inventory System, Web Data, Android Applications.